Complexo Lutjanidae/Epinephelidae (Teleostei: Perciformes): variação espaço temporal da captura na plataforma, talude e bancos oceânicos do nordeste - Lima, Sandy Evelin Rodrigues (2024)
Brazil has 8 thousand km of coastline, between the states of Amapá and Rio Grande do Sul, with considerable biodiversity on the continental shelf and ocean banks. These regions are fundamental for fishing activity, as they bring together several species of high commercial value, such as those from the Lutjanidae and Epinephelidae families. These are exploited in fisheries of various scales, where artisanal fishing carried out in the Northeast region has a strong impact on these species, as they have a wide distribution, ranging from the reefs of the platform to the continental slope and ocean banks. The present study aimed to analyze the spatio-temporal variation in the production of the Lutjanidae/Epinephelidae complex, originating from a longline vessel operating on the northeastern coast. The data used were obtained using onboard maps referring to 53 cruises carried out by a national vessel between 2004 and 2011. The trips totaled 569 days, with a median of 13 days, which could vary between 2 and 22. It was observed that production per family in each feature varied significantly across the slope. The production of the sirigado Mycteroperca bonaci differed between features, being influenced by the variation between slope and ocean banks. As for CPUE, a significant variation of lutjanids was detected between the features, where the lowest median was recorded on the platform, which was statistically different from that recorded on the slope and ocean banks. For epinephelids, the significant variation between features for CPUE was due to the highest median recorded on ocean banks. Therefore, these results are essential to collaborate in decision-making for the management of this fishery, since the capture of these targets revealed spatio-temporal distribution patterns in areas that are considered a “hotspot” of reef fish biodiversity, and which can have influences of possible aggregations on the captures made.